2010
DOI: 10.1021/om100736m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Reactivity of the Heterometallic Dinuclear μ-PH2and μ-PPhH Complexes FeMn(CO)8(μ-PH2) and FeMn(CO)8(μ-PPhH)

Abstract: Deprotonation of Fe(CO)4PRH2 and treatment with Mn(CO)5Br afforded the dinuclear complexes FeMn(CO)8(μ-PRH) (1a, R = H; 1b, R = Ph), which contain the relatively rare μ-PH2 and μ-PPhH functionalities. The heterometallic nature of these complexes was confirmed by mass spectrometry, and the molecular structures of 1a and 1b were determined by X-ray diffraction experiments. Deprotonation of 1b and subsequent addition of Mn(CO)5Br or AuPPh3Cl yielded the trinuclear complexes FeMn(CO)8[μ-PPh(Mn(CO)5)] (3a) and FeMn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…FTO glass (TEC 7, with resistivity of 6-8 Ω cm -2 ) was obtained from Hartford Glass Co. FeMn(CO)8(μ-PH2) was synthesized according to previous work. 39 Synthesis of TiO2 nanorod array. TiO2 nanorod arrays on fluorine-doped tin oxide (FTO) were grown through a hydrothermal process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FTO glass (TEC 7, with resistivity of 6-8 Ω cm -2 ) was obtained from Hartford Glass Co. FeMn(CO)8(μ-PH2) was synthesized according to previous work. 39 Synthesis of TiO2 nanorod array. TiO2 nanorod arrays on fluorine-doped tin oxide (FTO) were grown through a hydrothermal process.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we report a ternary TMP catalyst, FeMnP, synthesized via MOCVD from the single-source precursor FeMn(CO)8(µ-PH2). 39 FeMnP was deposited on a three-dimensional TiO2 nanorod array photoanode to form a TiO2/FeMnP core/shell nanostructure. As a result, dramatically enhanced PEC performance was achieved with the core/shell nanorod array photoanode.…”
mentioning
confidence: 99%
“…Several papers by the groups of Haupt [33], Scheer [34], Whitmire [35], Glueck [36] and Mays [37] also dealt with deprotonation of PHR-bridged dinuclear complexes which, as judged from trapping experiments with halocomplexes or other electrophiles, led to the formation of intermediate anionic phosphinidene complexes. However, most of these intermediates were poorly characterised and unstable species for which even their solution structures could not be defined clearly.…”
Section: Scheme 12mentioning
confidence: 99%
“…The organometallic precursor FeMn(CO)8(µ-PH2) was synthesized and used as the single-source precursor for the deposition of FeMnP nanoplatelets on both nickel foam (NF) and graphene-coated nickel foam (GNF) using a homemade MOCVD setup ( Fig. S1) [32,36]. The high quality of the CVD grown GNF was confirmed by the negligible D band in its Raman spectra, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the SSP-MOCVD method was used to grow FeMnP on TiO2-nanorod arrays for photoelectrochemical OER, and it was found that the TiO2/FeMnP core/shell structure remained stable at the theoretical photocurrent density of TiO2 [34,35]. In the present work, we used the SSP-MOCVD to grow nanostructured ternary FeMnP from the volatile precursor FeMn(CO)8(µ-PH2) [36] onto nickel foam (NF) and graphene-protected nickel foam (GNF), and demonstrated FeMnP as a bifunctional catalyst for efficient and stable overall water splitting. Here, the SSP-MOCVD for the synthesis of a TMP on a conductive substrate is presented as an effective route to meeting the necessity of stable, high surface area structures with metallic cores for catalysis.…”
Section: The Deposition Of the Tmp By Metal-organic Chemical Vapor Dementioning
confidence: 99%